Concept & Application of Baiʻ al-Īnah in Islamic Banking in Indonesia and Malaysia - Istianah ZA (Varia Justicia, 2020)
Baiʻ al-īnah is the process of buying and selling carried out by the seller to the buyer on a direct or credit basis, which then the goods are resold by the buyer to the original seller at a price lower than the previous purchasing price. This research is normative (doctrinal) research, with a regulative (statute approach) and conceptual approaches, emphasizing the use of secondary data in the form of primary, secondary, and tertiary legal materials. The result shows that: First, the scholars had different opinions on baiʻ al-īnah. Abu Hanifah forbade baiʻ al-īnah from the legally binding sale, and the purchase was illegal. Hence the second sale and purchase were also illegal. Besides, Imam Malik and Ahmad ibn Hanbal also prohibited baiʻ al-īnah because they both adhered to the arguments of sadd aż-żrīʻah, where baiʻ al-īnah contained elements of usury, manipulation to justify baiʻ al-īnah interest. In contrast, Imam al-Syafi'i allowed baiʻ al-īnah because buying and selling were halal (legal), and based on qiyas, the buying and selling model was in line with the law of buying and selling according to the Al-Qur'an. However, al-Syafi'i also prohibited baiʻ al-īnah if any hilah/manipulations occur. Second, Indonesia prohibits baiʻ al-īnah to be applied in Islamic Financial Institutions (LKS), except for one type of baiʻ al-īnah in an emergency case, the for transferring customer debts from Conventional Financial Institutions (LKK) to LKS. Meanwhile, in Malaysia, baiʻ al-īnah can be applied to Islamic financial institutions because Malaysia refers to the opinion of Imam al-Syafi'i. Despite that, Malaysia continuously evaluates the program and regulates baiʻ al-īnah to be applied cautiously. Baiʻ al-īnah in Malaysia is practiced in several Islamic products, including Islamic credit card financing, home financing, gold transactions,etc.